Teachers’ professional development maximized by collaborative context for teaching and learning statistics - Conti, Keli Cristina; Carvalho, Dione Lucchesi de; Carvalho, Carolina Fernandes de (Revista Eletrônica de Educação, 2016)
<!--[if gte mso 9]> <![endif]--> This article seeks to systematize some reflections resulting from a doctoral research that aimed to understand the process of professional development from the perspective of statistical literacy in collaborative contexts, showing evidences of professional development of members from a group of teachers and future teachers of Early Childhood Education and initial years of Elementary School. Based on a qualitative approach, it is a case study of the Group "Estatisticando". Although the writing and sharing of experiences by the participants were not requirements, this process happened and became powerful extending beyond the group meetings, resulting in the publication of narrative texts, an article and some participations in events. Therefore, the professional development of one of the group members will be detailed, from her narratives analysis. The collaborative context created and the study group journey also showed that teachers and future teachers can investigate their own practice so that they can develop themselves professionally. Keywords: Statistics – study and teaching. Teacher professional development. Collaborative group. Literacy. <!--[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:8.0pt; mso-para-margin-left:0cm; line-height:107%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] -->